2018
DOI: 10.3390/rs10091426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Stability of the Darbandikhan Dam after the 12 November 2017 Mw 7.3 Sarpol-e Zahab (Iran–Iraq Border) Earthquake

Abstract: We used a global positioning system (GPS), levelling, and Sentinel-1 data to evaluate the stability of the Darbandikhan dam in northeast Iraq after the 2017 Mw 7.3 Sarpol-e Zahab earthquake. GPS and levelling datasets collected in March and November 2017 were used to compute the co-seismic surface displacements of the dam. Sentinel-1 synthetic aperture radar (SAR) images collected between October 2014 and March 2018 were employed to recover the displacement time series of the dam. The large-magnitude displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Previous work (e.g., [2,36,41]) highlighted the capability of satellite techniques for dam monitoring. This research aims to emphasise that comprehensive monitoring is achievable using satellite techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work (e.g., [2,36,41]) highlighted the capability of satellite techniques for dam monitoring. This research aims to emphasise that comprehensive monitoring is achievable using satellite techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring of dam displacements plays a crucial role in the detection of unsafe conditions, requiring appropriate management actions and/or counteractive measures from the early stages [1]. Indeed, the early detection of a dam instability should constitute a key component of any dam maintenance plan and could lead to structural stabilisation to prevent any initial warning from turning into a disaster [2].…”
Section: Introductionmentioning
confidence: 99%
“…While monitoring of individual infrastructure is critical, the regional-scale monitoring of infrastructure is hypercritical for land use planning and sustainable development. Studies have shown the application of satellite-based Interferometric Synthetic Aperture Radar (InSAR) for monitoring bridges and critical infrastructure as well as regional-scale displacement from tectonics and other processes [8][9][10][11][12]. This study builds on those efforts to demonstrate how InSAR based (particularly Persistent Scatterer Interferometry (PSI)) monitoring and Geographic Information System (GIS) based analysis can be helpful to understand the performance of an individual infrastructure as well as evaluate whether regional scale processes control these performances.…”
Section: Introductionmentioning
confidence: 97%
“…Also, correlation between changes of reservoir surface, obtained by remote sensing methods, with obtained GNSS displacements was calculated in this study and results showed weak positive correlation between tested variables [7]. Levelling, GPS measurements and SAR images are used to evaluate stability of the Darbandikhan dam (Iraq) after high magnitude earthquake in research conducted by Al-Husseinawi et al (2018). Their research concludes that SAR images of the post-seismic dam deformation are useful to inform maintenance plans, but terrestrial surveys are still essential in the case of large-gradient deformation during earthquakes [8].…”
mentioning
confidence: 96%
“…Levelling, GPS measurements and SAR images are used to evaluate stability of the Darbandikhan dam (Iraq) after high magnitude earthquake in research conducted by Al-Husseinawi et al (2018). Their research concludes that SAR images of the post-seismic dam deformation are useful to inform maintenance plans, but terrestrial surveys are still essential in the case of large-gradient deformation during earthquakes [8].…”
mentioning
confidence: 99%